To the inventory of Ukraine’s defense lands - Kustovska О.; Mudra, S. (Land Management, Cadastre and Land Monitoring, 2020)
The article analyzes the inventory of the defense lands of Ukraine, which involves establishing the location of objects and their boundaries, because the implementation at the proper level of governmental functions of the state in the planning, monitoring and control over the use and protection of land depends on the availability of complete, objective and sufficient information about them. The offenses faced by land users of such land plots, in particular, are unauthorized occupation of land and unauthorized construction, seizure of land through registration of ownership of real estate objects, reduction of rent for land etc. The procedure of conducting land inventory, which regulates the requirements for carrying out land inventory during the implementation of land management and preparation of technical documentation, in particular, the Decree of the Cabinet of Ministers of Ukraine No. 476 «On Approval of the Procedure for Land Inventory and Recognition Of the Cabinet of Ministers of Ukraine» of June 5, 2019. The work done on the inventory of land and real estate of the Armed Forces of Ukraine for the period 2014-2019 has been evaluated. Positive aspects of correction and filling of the real estate database started three years ago in the Ministry of Defense of Ukraine for creation of automated workplaces of managers to support effective management of real estate and infrastructure network were noted, since the availability of systematic information about state-owned and owned land plots in the operational management of the Ministry of Defense of Ukraine depends on Ukraine’s fulfillment of international obligations, which is an indisputable argument for yst of the state land inventory defense promptly. Keywords: inventory, land, property, defense lands, Ukrainian Armed Forces, land management projects.